2022
DOI: 10.21203/rs.3.rs-1285516/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Irisin enhances chondrogenic differentiation of human mesenchymal stem cells via Rap1/PI3K/AKT axis.

Abstract: BackgroundHuman mesenchymal stem cells (hMSCs) have been proven to have inherent chondrogenic differentiation potential, which appears to be used in cartilage regeneration. Increasing evidence suggests that irisin enhances osteoblast differentiation of MSCs, but little is known about its potential on chondrogenic differentiation. MethodsIn our study, we investigated the effects of irisin on chondrogenic differentiation of hMSCs, and detected the underlying mechanism using RNA-seq.ResultsCompared with the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In a group of postmenopausal women with low bone mass, irisin levels in the circulation closely correlated with bone mineral status and osteoporotic fracture risk [16], suggesting that irisin may act as a biochemical marker of bone mineral-related diseases. Further studies confirmed the potential effects of irisin on bone metabolism by indicating that irisin could not only prevent the inhibition of osteoblast differentiation under stimulated microgravity conditions but also enhance the osteogenic and chondrogenic differentiation of MSCs by modulating the Wnt/βcatenin signaling pathway [17][18][19]. However, the effect of irisin on cell injuries and ASC osteogenic differentiation under hyperglycemic conditions is not fully understood.…”
Section: Introductionmentioning
confidence: 94%
“…In a group of postmenopausal women with low bone mass, irisin levels in the circulation closely correlated with bone mineral status and osteoporotic fracture risk [16], suggesting that irisin may act as a biochemical marker of bone mineral-related diseases. Further studies confirmed the potential effects of irisin on bone metabolism by indicating that irisin could not only prevent the inhibition of osteoblast differentiation under stimulated microgravity conditions but also enhance the osteogenic and chondrogenic differentiation of MSCs by modulating the Wnt/βcatenin signaling pathway [17][18][19]. However, the effect of irisin on cell injuries and ASC osteogenic differentiation under hyperglycemic conditions is not fully understood.…”
Section: Introductionmentioning
confidence: 94%